Acyclic Cucurbit[n]uril‐Type Molecular Containers: Influence of Linker Length on Their Function as Solubilizing Agents. (15th March 2016) - Sigwalt, David; Moncelet, Damien; Falcinelli, Shane; Mandadapu, Vijaybabu; Zavalij, Peter Y.; Day, Anthony; Briken, Volker; Isaacs, Lyle
Abstract: Two acyclic cucurbit[ n ]uril (CB[ n ])‐type molecular containers that differ in the length of the (CH2 ) n linker (M2C2 : n =2, M2C4 : n =4) between their aromatic sidewalls and sulfonate solubilizing groups were prepared and studied. The inherent solubilities ofM2C2 (68 mm ) andM2C4 (196 mm ) are higher than the analogue with a (CH2 )3 linker (M2, 14 mm ) studied previously. 1 H NMR dilution experiments show thatM2C2 andM2C4 do not self‐associate in water, which enables their use as solubilizing excipients. We used phase solubility diagrams (PSDs) to compare the solubilizing capacities ofM2, M2C2, M2C4, hydroxypropyl‐β‐cyclodextrin (HP‐β‐CD), and sulfobutylether‐β‐cyclodextrin (SBE‐β‐CD) toward 15 insoluble drugs. We found thatM2C2 andM2C4 —as gauged by the slope of their PSDs—are less potent solubilizing agents thanM2 . However, the higher inherent solubility ofM2C2 allows higher concentrations of drug to be formulated usingM2C2 than withM2 in several cases. The solubilizing ability ofM2C2 and SBE‐β‐CD were similar in many cases, with K rel values averaging 23 and 12, respectively, relative to HP‐β‐CD. In vitro cytotoxicity and in vivo maximum tolerated dose studies document the biocompatibility ofM2C2 . Abstract : A solution for all : Acyclic cucurbit[ n ]uril‐type molecular containers function as solubilizing excipients for insoluble drugs. The influence of the length of the linker between the aromatic wall and the sulfonate solubilizing group (e.g.M2C2, M2, M2C4 ) on the containers′ inherent aqueous solubility and recognition properties toward insoluble drugs are presented.M2C2 does not display significant in vitro cytotoxicity, and a maximal tolerated dose study indicatesM2C2 is well tolerated in mice.